Hemipilia galeata (Orchideae, Orchidaceae), a new species from Fujian Province, southeastern China - Tang, Ying; Zhu, Xin-Xin; Peng, Hua; Ma, Jin-Shuang (Phytotaxa, 2016)
A new orchid species, Hemipilia galeata, is described and illustrated from Wuyi Mountains, Fujian Province, southeastern China, and included in a phylogenetic analysis using the nuclear ribosomal ITS and three plastid markers (matK, trnL intron and trnL-F spacer) DNA. This species is a member of H. section Hemipilia sensu Tang et al. and is distinguished from other species in Hemipilia by its hemispheric dorsal sepal. It is similar to H. hemipilioides, H. occidensichuanensis and H. thailandica, but H. galeata differs by its elliptic, purple-spotted leaf, suborbicular petals, oblong lateral lip lobes and an ovate midlobe.